The Alevi Diaspora – Its emergence as a political actor and its impact on the homeland - Arslan, Zeynep (Border Crossing, 2016)
<span style="line-height: 107%; font-family: 'Times New Roman','serif'; font-size: 12pt; mso-fareast-font-family: 'Times New Roman'; mso-ansi-language: EN-GB; mso-fareast-language: DE-AT; mso-bidi-language: AR-SA;" lang="EN-GB">Through comparative literature research and qualitative analysis, this article considers the development of Alevi identity and political agency among the diaspora living in a European democratic context. This affects the Alevi emergence as political actors in Turkey, where they have no official recognition as a distinct religious identity. New questions regarding their identity and their aspiration to be seen as a political actor confront this ethno-religious group defined by common historical trauma, displacement, massacre, and finally emigration.